Reflecting Experiences on Using Blended Learning: A Self Narrative Inquiry Research - Farani, Rizki (Jurnal Kiprah, 2021)
Blended learning (BL) has widely implemented in higher education setting. However, the application of BL presents a wide range of variation. BL is conducted based the consideration of modalities, methods and instruction. As the impact, each instructor has different strategies in applying BL. Therefore, it is important to explore BL practices in order to recognize strength and weakness of BL in different context. In this self-narrative inquiry research, I would like to narrate my personal experience in implementing BL on some theoretical courses in a bachelor program. The stories cover my BL practices from 2015 until 2019 which explain about modalities, methods and instructions selections. In narrating my stories, I highlight benefit and challenges of every BL practice to emphasize personal reflection from past, present and future events. By connecting three life events, I offer a reflection on how to select effective BL practice based on technical considerations, teaching strategies and instructional design. The reflection is expected to provide a reference for educators in designing blended learning for higher education.